Case Series: COVID-19 in African American Patients With Sarcoidosis - Manansala, Michael; Ascoli, Christian; Alburquerque, Ana Goico; Perkins, David; Mirsaedi, Mehdi; Finn, Patricia; Sweiss, Nadera J. (Frontiers in Medicine, 2020)
Data on the clinical presentation and outcomes of sarcoidosis patients with coronavirus disease 19 (COVID-19) are scarce. In this case series, we identified 5 out of 238 sarcoidosis patients who are enrolled in an ongoing longitudinal observational study who developed COVID-19 during the study period and follow their clinical course. Four patients recovered completely, whereas one patient expired during hospital admission. Our preliminary experience suggests that African American patients with chronic sarcoidosis treated with disease-modifying anti-rheumatic drugs (DMARDs) or anti-tumor necrosis factor (TNF) therapy do not seem to be at increased risk of respiratory or life-threatening complications from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) compared with the general population, although at the present time, we advocate for maintaining a high level of vigilance and strict follow-up in this patient population.